“El límite de intervención delictiva en el ejercicio de defensa de los procesados en delitos de criminalidad organizada” - Perez Azabache, James Aldrin (2019)
ABSTRACT The present investigation entitled “the limit of criminal intervention in the exercise of defense of those prosecuted in crimes of Organized Criminality” determines the limit between the punishable and non-criminally punishable acts of those who provide legal services for a criminal organization. To arrive at the hypothesis that the limit of criminal intervention in the exercise of defense of those prosecuted in crimes of Organized Crime, is the realization of neutral activities in the exercise of legal sponsorship, it was determined what the limit of nonpunitive action of the lawyer within a criminal organization, according to the judgments of the Supreme Court. For this, the 7 cases that were resolved by the Supreme Court regarding the limits of criminal intervention were analyzed, identifying the most important qualities such as: type error, safety of conduct, compliance with the function and subjective aspects, such as founding elements of the objective atypicality of behavior. With this objective, the universal method, embodied in the research model presented, the general method, the deductive method with which the founding elements of atypicality in each of the sentences, the inductive method with which we were able to be found was used appreciate that the elements found were applicable to the entire sentence. This is how legislative decree No. 1106, organized criminality and criminal charges, philosophical foundations of the limits to criminal intervention, the limits of criminal intervention and the lack of action in jurisprudence were developed. Finally, it is concluded that the limits of punishability and non-punishability of the lawyer's own conduct in the criminal organization are based on the innocuous nature of his conduct.